Non-compete clause: a comparative study - Reem Ahmed Al-Zahrani (International Journal of Law Research and Studies, 2025)
This study aims to analyze the employee's contractual obligation not to compete after the expiration of the employment contract, regulated by the so-called non-competition clause. This is achieved by comparing the Saudi and Egyptian labor laws, particularly in light of Article (83) of the Labor Law. The study adopts an analytical approach, alongside a comparative approach, with the aim of clarifying the obstacles to employers' adherence to the non-competition clause and the adequacy of regulating this clause in the Saudi labor law. The study concludes with several findings, the most important of which is that the Saudi labor law does not stipulate that the employee must have full legal capacity upon contracting. The study also makes several recommendations, most notably: We recommend stipulating and regulating the cases in which the employer may not adhere to the non-competition clause. We also recommend obligating the employer to provide the employee with fair compensation for their adherence to the non-competition clause to ensure balance in contractual obligations.
Keywords: Contractual Obligation of the Employee; Non-Competition; Employment Contract; Saudi Labor Law; Egyptian Labor Law